2017
DOI: 10.21511/ppm.15(2).2017.01
|View full text |Cite
|
Sign up to set email alerts
|

Organizational attractiveness: an empirical study on employees attitudes in lithuanian business sector

Abstract: Measurement of employer’s attractiveness has been given much attention in many countries all over the world, but there was no extensive research performed in Lithuania so far, providing empirical evidence to define the landscape of organizational attractiveness in Lithuanian business sector. The aim of this study (N = 1020 respondents) is to identify which dimensions make organizations attractive as employers in Lithuanian business sector. The article employs a research approach based on a postpositivistic per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…The theoretical review reveals that there is no single standard list of employer attractiveness dimensions that an employer value proposition should compile that can be applied to all countries ( Bakanauskiene et al., 2017 , 2019 ). Moreover, if “blueprints” for attractive dimensions existed, any attempt to copy others would not provide a unique competitive edge ( Moroko and Uncles, 2008 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The theoretical review reveals that there is no single standard list of employer attractiveness dimensions that an employer value proposition should compile that can be applied to all countries ( Bakanauskiene et al., 2017 , 2019 ). Moreover, if “blueprints” for attractive dimensions existed, any attempt to copy others would not provide a unique competitive edge ( Moroko and Uncles, 2008 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…From this point of view, it is important to understand what attracts a job seeker. Organizational attractiveness is also considered the power that motivates an applicant to focus on an employer brand and encourages existing employees to stay (Bakanauskiene, Bendaravičienė, & Barkauskė, 2017), as well as the degree to which potential and current employees perceive the organization as a good place to work (Jiang & Iles, 2011). Ehrhart and Ziegert (2005) have defined organizational attraction as the process of getting candidates to view the organization as a positive place to work and have examined it from the applicant's perspective.…”
Section: Organizational Attractivenessmentioning
confidence: 99%
“…The five items measurement scale was also used by Kausel and Slaughter (2011) to examine whether the use of narrow personality facets, such as trust (under the Big Five trait agreeableness), assertiveness (under extraversion), and imagination (under openness to experience) enhances the prediction of attraction. Bakanauskiene et al (2017) data analysis revealed that 19 employer attributes are positively linked to organisational attractiveness. However, we use the scale developed by Berthon et al (2005) because it has been more frequently used in subsequent studies (Alnıaçık & Alnıaçık, 2012;Arachchige & Robertson, 2011;Germano et al, 2016;Sivertzen et al, 2013).…”
Section: Employer Attractivenessmentioning
confidence: 99%
“…Economic Value (EV): excellent promotion opportunities within the organisation, above-average basic salary, an attractive overall compensation package. Development Value (DV): provides recognition, self-worth and confidence, the development of skills and career-enhancing experiences (Bakanauskiene et al, 2017;Berthon et al, 2005;Dabirian et al, 2017;Dabirian et al, 2019;Germano et al, 2016).…”
Section: Employer Attractivenessmentioning
confidence: 99%